The Elusive Origin of Atherosclerotic Plaque Calcification - Canet-Soulas, Emmanuelle; Bessueille, Laurence; Mechtouff, Laura; Magne, David (Frontiers in Cell and Developmental Biology, 2021)
It has been known for decades or even centuries that arteries calcify as they age. Vascular calcification probably affects all adults, since virtually all have atherosclerotic plaques: an accumulation of lipids, inflammatory cells, necrotic debris and calcium phosphate crystals. Much more recently, it was discovered that, despite the received wisdom, heavily calcified plaques are likely more stable than younger plaques with diffuse microcalcification, which seem to be more prone to rupture and thus to trigger a cardiovascular event. What remains to be discovered is how these early microcalcifications form. Several very different origins have been recently suggested, and to date there is little to show that one is more likely than another. In this context, we will first review articles reporting the location and features of early microcalcifications, and then review the putative mechanisms that have been suggested to explain their formation.